Assisted implant stabilization using a modified microplate fixation technique - Mohamed Hamdy Helal; Ahmed Noaman Ali; Eman Abd El Raouf Tawfik; Mostafa Mahmoud Youssef Mohamed; Moustafa Nabil Aboushelib (Journal of Oral Biology and Craniofacial Research, 2025)
Objectives: In many clinical cases, the surgical defect around the osteotomy does not grant sufficient stability which may compromise the inserted dental implant. Using a fixation microplate may solve this issue by improving the stability of the inserted implant. This study aimed to evaluate assisted implant stability using microplate fixation in compromised bone defects. Methods: Two osteotomy defects (6 mm and 4 mm in diameter) were made in the femur of a dog model. Dental implants (4 mm in diameter and 10 mm in length) were placed in the two defects. Microplates were used to enhance the initial stability of the compromised implant placed in the larger defect size without the need for the additional use of a bone graft. A reverse torque test and histomorphometric analysis were performed after eight weeks to assess bone implant contact (n = 48). Results: Both plate and control implants had almost identical bone-to-implant contact ratios, 82.55 ± 0.61 and 82.86 ± 0.69, respectively. The two tested implants had no statistically significant difference in bone implant contact (t = 1.155, P = .260) nor reverse torque test (t = 1.408, P = .173). Conclusions: Assisted implant stabilization improved osteointegration of implants suffering from poor initial stability without the need to resort to bone graft or other complicated techniques.